4 posts • Page 1 of 1
Since you are given the wavelength you can solve for the frequency since the c in this equation is a constant c=(wavelength)(frequency). Then the Energy equation is E=h*(frequency). Since you just found frequency and h is a constant then you can solve for the energy. Or you can simply just use the equation E=hc/(wavelength) if you want to do it in one step.
Like everyone has said, just because there is not a given equation for energy in terms of what is given doesn't mean that you can't rearrange two equations to obtain what you want. Combine the equations E=h(frequency) and c=v (frequency)
Who is online
Users browsing this forum: No registered users and 3 guests